Mitochondrial respiratory capacity remains stable despite a comprehensive and sustained increase in insulin sensitivity in obese patients undergoing gastric bypass surgery. (12th February 2018) - Lund, M. T.; Larsen, S.; Hansen, M.; Courraud, J.; Floyd, A. K.; Støckel, M.; Helge, J. W.; Dela, F.
Abstract: Aim: It has been proposed, but not yet demonstrated by convincing evidence in published articles, that insulin resistance and mitochondrial respiratory function are causally related physiological phenomena. Here, we tested the prediction that weight loss–induced increase in insulin sensitivity will correlate with a corresponding change in mitochondrial respiratory capacity over the same time period. Methods: Insulin sensitivity was evaluated using the hyperinsulinaemic‐euglycaemic clamp technique, and skeletal muscle mitochondrial respiratory capacity was evaluated by high‐resolution respirometry in 26 patients with obesity. Each experiment was performed ~2 months and 1‐2 weeks before, and ~4 and ~19 months after Roux‐en‐Y gastric bypass (RYGB) surgery. Results: A substantial weight loss was observed in all patients, and insulin sensitivity increased in all patients over the 21‐months time period of the study. In contrast, skeletal muscle mitochondrial respiratory capacity, intrinsic mitochondrial respiratory capacity and mitochondrial content remained unchanged over the same time period. Conclusion: Among obese patients with and without type 2 diabetes undergoing RYGB surgery, intrinsic mitochondrial respiratory capacity in skeletal muscle is not correlated with insulin sensitivity before or after the surgical intervention. Mitochondrial respiratory function may not be germane to the pathophysiology and/or aetiology of obesity and/or type 2 diabetes.